2006
DOI: 10.1038/sj.bjc.6603273
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate used in combination with aminolaevulinic acid for photodynamic killing of prostate cancer cells

Abstract: Photodynamic therapy (PDT) using 5-aminolaevulinic acid (ALA) to drive production of an intracellular photosensitiser, protoporphyrin IX (PpIX), is a promising cancer treatment. However, ALA-PDT is still suboptimal for thick or refractory tumours. Searching for new approaches, we tested a known inducer of cellular differentiation, methotrexate (MTX), in combination with ALA-PDT in LNCaP cells. Methotrexate alone promoted growth arrest, differentiation, and apoptosis. Methotrexate pretreatment (1 mg l À1 , 72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 35 publications
3
116
0
1
Order By: Relevance
“…anand et al reported that methotrexate (Mtx) stimulated the accumulation of an intracellular photosensitizer, protoporphyrin Ⅸ, and enhanced the antitumor effect of PDT using 5-aminolaevulinic acid (ala), but that ala-PDt followed by Mtx yielded no enhancement in tumor cell lethality (42,43). in the present study, as shown in fig.…”
Section: Discussionsupporting
confidence: 48%
“…anand et al reported that methotrexate (Mtx) stimulated the accumulation of an intracellular photosensitizer, protoporphyrin Ⅸ, and enhanced the antitumor effect of PDT using 5-aminolaevulinic acid (ala), but that ala-PDt followed by Mtx yielded no enhancement in tumor cell lethality (42,43). in the present study, as shown in fig.…”
Section: Discussionsupporting
confidence: 48%
“…We measured the amount of PpIX using fluorescence intensity analysis instead of direct PpIX measurement, thinking the former might have advantages in fluorescence quantification over other detection methods 10,16,23 Our results of the association between CDH13 expression and amount of intracellular PpIX in cell lines and tumor specimens strongly suggested that the CDH13 might act on PpIX accumulation. Results clearly demonstrated that CDH13 siRNA caused an increase of PpIX accumulation and 5-ALA-induced fluorescence in glioma cells, suggesting that CDH13 downregulation can improve the accuracy of PpIX fluorescence-guided discrimination of malignant cells.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that the induction of differentiation enhanced PpIX accumulation in some cell lines, such as prostate cancer cells (51), fibroblasts, B16 cells (42) and keratinocytes (52). However, the relationship between tumour cell differentiation and photosensitizer accumulation is poorly defined (53) since some differentiation agents, such as butyrate, did not enhance PpIX accumulation whereas others, such as hexamethylene bisacetamide (HMBA) and methotrexate, did (43,54). To the best of our knowledge, this is the first evidence that a member of the coumarin group enhanced PpIX accumulation at least in melanoma cells; this observation was not reproduced in SW620 cells suggesting a cell-type specific effect.…”
Section: Discussionmentioning
confidence: 99%